Models in order to control the sport for all in the schools of Pinar del Río County - María Antonia Afre-Socorro; Yardleys Noda-Rabelo; Zaire Bolufe-Fernández (Podium, 2016)
The study is started upon detecting in the visits of Pinar del Rio county´s schools that in the controls that were effected to the sport for all, diversity of standard for their evaluation were found, per party of methodologists, directors of school, sport cocktails and professors. The utilization of scientific methods facilitated the study of the theoretical foundations, apply instruments in order to determine the inadequacies and elaborate models for unifying evaluative criterions by establishing frequencies of difficulties. The implementation of this model in all the municipalities during three school courses has shown satisfaction because of the work of people in charge of controlling the activities became easier.